(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
In this paper, a L-shaped SDRA (Square dielectric resonator antenna) for 5G mm-wave application is proposed. The antenna is a square L-shaped structure with an increased realized gain and that supports the 24-34 GHz frequency ranges with broadband with fractional bandwidth of 13.8% from 26.3Hz to 30.2 Hz and two narrow bands, constructing a quad-band antenna. The observed gain is approximately 8dB. Simulations and design using commercial software CST Studio Suite that have been performed to confirm the viability of the suggested SDRA for the next fifth-generation (5G) wireless networks.